Identificación y evaluación del potencial fitorremediador de especies vegetales presentes en el suelo contaminado por grasas y aceites lubricantes en la lavadora y lubricadora marifer de la ciudad de Zamora - Rivas Rodríguez, Juan Carlos (2016)
The present research work was developed near the lubricant and washing car Marifer in the city of Zamora, was based on the technique of phytoremediation for the removal of Total Petroleum Hydrocarbons (TPH), Fats and Oils present in the soil at concentrations of 14921.7 and 15318.2 mg/kg, values above the maximum permissible limits. In addition, the productivity of the zone was determined finding cassava, maize, banana and sugarcane crops with a production of 0.69 T/Ha, which is low compared to the national production of 77.47 T/Ha. Subsequently an herbaceous inventory and a taxonomic analysis were carried out where the species Ageratum conyzoides L. and Sida rhombiofolia L, were identified, as representative of the study and pollution area. To start the treatment of phytoremediation, a greenhouse of 12m was installed. In addition, five platforms of 0.36 m were installed where the contaminated soil extracted from contamination points was deposited. For the transplant, 32 plants per plant species were collected by immersing them in a solution of 50 ml of Cytokin with 50 g of SOL-U-GRO in 20 liters of water for one minute, two treatments were implemented with two replicates for each plant species, being evaluated to determinate their behavior to contaminate during the 90 days of the present investigation. The Ageratum conyzoides L. specie, presented more anomalies and a mortality rate of 25%, compared to the species Sida rhombifolia. L, wich presented less anomalies and there was no mortality among its plants. Regarding the removal of contaminant the specie Ageratum conyzoides. L, stood out with 25.51% for TPH and 25.48% of fats and oils against the specie Sida rhombifolia. L that presented a reduction of 18.23 TPH and 16.43% of Fats and Oils. This plant species had demonstrate to have a phytoremediation potential for the removal of TPH, Fats and Oils, so they can be applied for the decontamination of soils with a cost per hectare of 1,261.13 dollars, considering that these species once implemented in the area to be decontaminated does not need constant care.